Full Digital Workflow in the Esthetic Dental Restoration - Suchada Kongkiatkamon; Dinesh Rokaya (Hindawi Limited, 2022)
This case report presented a fully digital workflow in esthetic dental restoration. A 51-year-old female patient was referred to BDMS Wellness Clinic due to a fracture of the maxillary left central incisor. An immediate dental implant was planned to restore tooth 21 with esthetic crown lengthening of upper front teeth and new zirconia crowns for teeth 11, 12, 13, 21, 22, and 23. Digital impression was made using a digital scanner (PRIMESCAN®, Dentsply Sirona, Bensheim, Germany); surgical guide (Cerec Guide 3, Dentsply Sirona, Bensheim, Germany) was designed by using a designing software (Galileos Software, Dentsply Sirona, Bensheim, Germany) and was milled by using a milling machine (MCXL milling machine, Dentsply Sirona, Bensheim, Germany) to create a precise surgical guide. 3D smile design was done by using the Digital Smile Design (DSD) program, the crown lengthening guide was designed according to DSD designed by using a designing software (Inlab 19 Software, Dentsply Sirona, Bensheim, Germany), and the guide was fabricated by a 3D printer (FormLabs Form 2, Formlab, MA, USA). Provisional crowns (splinted) for teeth 11, 12, 13, 21, 22, and 23 were milled by using polymer (VIPI BLOCK TRILUX®, VIPI Industria, Pirassununga, SP, Brazil) using a milling machine (MCX5, Dentsply Sirona, Bensheim, Germany). The zirconia crowns were designed by using software (Inlab19 Software, Dentsply Sirona, Bensheim, Germany) and milled using the same milling machine. At the implant position, Ti-base is cemented by using an abutment (Multilink Hybrid Abutment, Ivoclar Vivadent, Schaan, Lichtenstein, Germany) with zirconia coping (Cercon base white shade, Dentsply Sirona, Bensheim, Germany) utilized as the abutment. The zirconia crowns (Cercon Xt, Dentsply Sirona, Bensheim, Germany) were sintered and characterized and then cemented. The patient was satisfied with the esthetic outcome of the treatment.